Adsorption mechanisms and effects of thiocarbamate collectors in the separation of chalcopyrite from pyrite minerals: DFT and experimental studies. (January 2022) - Mkhonto, Peace P.; Zhang, Xingrong; Lu, Liang; Xiong, Wei; Zhu, Yangge; Han, Long; Ngoepe, Phuti E.
Graphical abstract: Abstract: We employed computational density functional theory (DFT) and microflotation tests complemented by analysis of electronic properties and X-ray photoelectron spectroscopy (XPS) data to investigate the adsorption mechanism of O-isopropyl-N-ethyl-thionocarbamate (IPETC), O-isopropyl-N-diethyl-thionocarbamate (IPDETC) and S-allyl-N-diethyl-dithiocarbamate (ADEDTC) on chalcopyrite reconstructed-(1 1 2) surface and pyrite (1 0 0) surface. The adsorption of the thiocarbamate collectors on chalcopyrite was observed to preferentially occur at Cu atoms instead of Fe atoms. The thiocarbamate collector adsorption on chalcopyrite Cu sites decreased in the order ADEDTC > IPDETC > IPETC, while on pyrite Fe sites, the adsorption strength decreased in the order ADEDTC > IPETC > IPDETC. This shows that the adsorption of ADEDTC was strong, although the adsorption on pyrite was weaker than the adsorption on chalcopyrite. In the associated microflotation tests, the chalcopyrite recoveries exceeded 90%, while the pyrite recoveries reached only 25%, with ADEDTC exhibiting the highest recoveries. XPS analysis of chalcopyrite treated and not with ADEDTC revealed that the adsorption of the ADEDTC S1 atom was stronger at Cu sites than at Fe sites. These findings provide a clear correlation between experiments and DFT predictions and therefore suggest that these thiocarbamate collectors may be useful in the floatation separation of chalcopyrite from pyrite minerals.